On Some Refinements of Bernstein Type Inequalities - Ahmad, Irshad; Liman, A. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
In this paper, we generalize some inequalities concerning to the Bernstein’s inequality for polynomials.